2014
DOI: 10.1007/s11552-014-9650-x
|View full text |Cite
|
Sign up to set email alerts
|

Mini-Open versus Extended open Release for Severe Carpal Tunnel Syndrome

Abstract: Background This study aims to compare surgical outcomes of severe carpal tunnel syndrome (CTS) treated with miniincision versus extensile release. Methods The method employed in this study was a retrospective review of patients with severe

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 38 publications
0
16
0
3
Order By: Relevance
“…An additional strength of this study is that each patient received the same intervention (mini-open CTR) performed by the same surgeon, which further limited confounding factors. Previous descriptions of the advantages of the mini-open approach have been published [8,9], but they either had a shorter follow-up or a smaller sample than this study. In our study, 11% of patients suffered from an early complication (within 3 months post-intervention) (Table 6), which is in accordance with the published rates in the literature, which range from 1% to 25% [10].…”
Section: Discussionmentioning
confidence: 99%
“…An additional strength of this study is that each patient received the same intervention (mini-open CTR) performed by the same surgeon, which further limited confounding factors. Previous descriptions of the advantages of the mini-open approach have been published [8,9], but they either had a shorter follow-up or a smaller sample than this study. In our study, 11% of patients suffered from an early complication (within 3 months post-intervention) (Table 6), which is in accordance with the published rates in the literature, which range from 1% to 25% [10].…”
Section: Discussionmentioning
confidence: 99%
“…The main complaint of the patients was about the scar of the surgery and the date of starting to use their hand in daily activities and return to work. 5,6,9,11,14,15,[18][19][20] Therefore, the later points were of interest for clinical analysis of the results of this study. The differences between both groups were statistically significant regarding the operative data.…”
Section: Resultsmentioning
confidence: 99%
“…Superiority among open or mini-open techniques for carpal tunnel release remains highly controversial in the orthopedic literature and among surgeons. Using a retrospective study, Murthy et al[ 7 ] reported no significant differences between the two procedures with regard to patient-rated symptom severity or functional status outcomes. Although this study presented a large cohort of severe CTS patients, they were not adequately matched between the two groups with regard to age, gender and preoperative electrodiagnostic testing.…”
Section: Discussionmentioning
confidence: 99%
“…The literature is virtually silent regarding comparison of mini-open and extended open release for CTS. To our knowledge, the only study by Murthy et al[ 7 ] compared these two approaches in patients with severe CTS. The confounding data in this study regarding severity of nerve compression that can be determined by electrodiagnostic testing let us design a matched-pair analysis to compare mini-open and extended open release techniques.…”
Section: Introductionmentioning
confidence: 99%